2021
DOI: 10.1016/j.drugpo.2021.103391
|View full text |Cite
|
Sign up to set email alerts
|

Living Under Coronavirus and Injecting Drugs in Bristol (LUCID-B): A qualitative study of experiences of COVID-19 among people who inject drugs

Abstract: Background : People who inject drugs (PWID) are a high-risk group for COVID-19 transmission and serious health consequences. Restrictions imposed in the UK in response to the pandemic led to rapid health and housing service alterations. We aimed to examine PWID experiences of: 1) challenges relating to the COVID-19 public health measures; 2) changes to opioid substitution therapy (OST) and harm reduction services; and 3) perceived effects of COVID-19 on drug use patterns and risk be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 26 publications
11
76
0
Order By: Relevance
“…The most prominent of the pandemic’s effects on both groups was its impact on mental health problems, which increased across groups. This finding is consistent with research studies that found higher rates of mental health issues during the pandemic in both the general population [ 48 50 ] and people who use drugs [ 25 , 27 , 51 ]. It is possible that social restrictions (prolonged lockdowns, isolation) and social services disruptions during the pandemic have affected participants’ sense of social connection and increased their levels of depression, anxiety, and suicidal thoughts.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The most prominent of the pandemic’s effects on both groups was its impact on mental health problems, which increased across groups. This finding is consistent with research studies that found higher rates of mental health issues during the pandemic in both the general population [ 48 50 ] and people who use drugs [ 25 , 27 , 51 ]. It is possible that social restrictions (prolonged lockdowns, isolation) and social services disruptions during the pandemic have affected participants’ sense of social connection and increased their levels of depression, anxiety, and suicidal thoughts.…”
Section: Discussionsupporting
confidence: 92%
“…PWID who were more stable prior to the pandemic (e.g., stable income, housing, and resources) were less vulnerable to the negative impacts of the COVID-19 lockdown and public health measures. This same study also shows how pandemic-related social isolation has exacerbated the deterioration of mental health conditions among PWID [ 25 ].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations